The influence of some plant extracts in control of fungi contaminating tissue culture media of date palm (Phoenix dactylifera L.) - Eman A. Al_Sawad (Journal of Kerbala for Agricultural Sciences, 2025)
The study aimed to isolate and diagnose the fungi associated with tissue palm growing media and their resistance to the method of poisoning the growing media of medicinal plants (cloves , ginger , currants , black seed) , compared with the effect of the chemical pesticide Beltanol . The results of isolation and diagnosis showed the dominance of the Aspergillus fungus in most of the samples under study and in a percentage appearance of 80% , while the rates of appearance of the rest of the species ranged between 40-60% . The outcomes of the test for pathogenicity in infecting the seeds of the four fungi that were chosen in this study showed that the seed germination rate was 0.0% and the seed inhibition rate was 100%, compared to the comparison treatment, which had a germination rate of 100% and an inhibition rate of 0.0% . The PCR analysis proved that the isolates belong to the fungi. Aspergillus niger , Penicillium chrysogenum, , Aspergillus flavus and Meyerozyma guilliermondii, as the isolates were recorded Fungi in the National Center for Biotechnology Information (NCBI) and under the special symbols (PQ895505.1 , PQ895508.1 , PQ895505.1 and PQ895494.1) respectively. The effectiveness of the pesticide Beltanol against the tested fungal isolates was studied, and showed that it was most effective on the two Fungi P. chrysogenum and A. flavus by 100% and 88% % respectively . the alcoholic clove extract at a concentration of 20% was superior in inhibiting fungi by 98.15% over the fungi A. niger, A. flavus, and P. chrysogenum, and 96.2% against the fungi. M. guilliermondii, and the aqueous extract of cloves at a concentration of 20% gave the highest antioxidant activity against the fungus A. flavus, at a rate of 88.88%, compared to the comparison treatment, which had an inhibition rate of 0.00%. The alcoholic extract inhibited the growth of the fungus at higher rates than the aqueous extract. The inhibition rates of the pathogens increase with increasing concentration of aqueous and alcoholic extracts.